Kaidah المشقه تجلب التيسير dan Penerapannya dalam Hukum Keluarga - Nur Suci Alawiyah; Mhd Amar Adly; Heri Firmansyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Because Islamic law is not mentioned directly in the Qur'an and Hadith, interpretation and contextualization through ijtihad are often necessary. To achieve this, Islamic jurisprudence must be integrated with current conditions and societal demands. This must be done in accordance with maqasid al-syariah, namely the aim of overcoming legal problems faced by individuals (mukallaf). Sharia guarantees the welfare of every person and is adapted to their abilities. It is stated in a hadith in the hadith of the Prophet narrated by Bukhari which means: "Religion makes things easy, the religion that Allah loves is the true and easy religion" (HR. Bukhari from Abu Hurairah) shows that Islam emphasizes the importance of ease in fulfilling religious obligations. According to the principle of المشقه تجلب التيسير, which means that difficulty brings ease, Islamic law is flexible to deal with the difficulties people face in worship and transactions. The concept of المشقه تجلب التيسير in the application of Islamic family law is explained in this paper using qualitative descriptive methodology and literature review techniques. Sources for this research include the Al-Qur'an, Hadith, tafsir, fiqh literature, and Qawaidul Fiqiyyah. To see how this principle is applied, this paper conducts a case study on Islamic family law. The aim of Al-Masyaqqah Tajlibut Taysir is to alleviate difficulties in the application of Islamic family law so that people can fulfill their obligations without experiencing due difficulties. This study identified seven categories of hardship (masyaqqah) that require relief (rukhsah), such as travel, illness, compulsion, forgetfulness, ignorance, general hardship, and deprivation. These categories guide legal experts in issuing fatwas and legal decisions to accommodate individual needs while upholding Islamic principles. In conclusion, المشقه تجلب التيسير serves as a basic principle in Islamic jurisprudence, facilitating the harmonization of Sharia with individual circumstances and societal needs, particularly in family law matters such as marriage contracts. Its application underscores the adaptability and compassion inherent in the principles of Islamic law, which promote justice and well-being for all individuals.